(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The movement of groundwater towards the Aral Sea is slowing down, which is one of the main reasons for the drying up of the Aral Sea. The Amudarya used to be a large collector, but the main reason is the lack of water, shallowness and sand.